Strategi Pencegahan dan Peningkatan Pengawasan BPOM Terkait Kasus Cemaran EG/DEG dalam Sirup Obat - Regina Liviandari; Patihul Husni (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Contamination of ethylene glycol and diethylene glycol (EG/DEG) is suspected to be the cause of the undesirable incident of acute kidney failure in children, which occurred in Indonesia in 2022. As the institution tasked with monitoring the distribution of medicines in Indonesia, the Food and Drug Supervisory Agency (BPOM) has taken scientifically based strategic, responsive, and professional steps in handling and controlling these cases. The purpose of this article is to provide an overview of prevention strategies and increased supervision carried out by BPOM in handling cases of EG/DEG contamination in medicinal syrups. This article review was prepared through a literature study of 22 pieces of literature published between 2013-2023. The results of the literature review show that BPOM has taken responsive and professional steps in the form of strengthening the pharmacovigilance system, ensuring quality assurance in the pharmaceutical industry, monitoring the import of propylene glycol and polyethylene glycol, strengthening pre-market, post-market, and enforcement supervision, and providing information to the public as a prevention strategy and increased supervision in handling cases of EG/DEG contamination.